ANALISA PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DAN MARKET EARNING VALUE PERUSAHAAN PROPERTY & REAL ESTATE LQ45 DI BURSA EFEK INDONESIA - Andi Martias (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study found that there is a corporate governance effect on earnings management practices in companies on the Indonesia Stock Exchange (IDX) as well as corporate performance messages or signals, especially on accrual opportunities. The results prove significant in limiting earnings management and earnings management as a message or signal of company performance, especially on accrual opportunities. The sample is an industrial company with the most shares on the IDX from 2019 to 2021. The sampling method uses a purposive random sampling method, namely: (1) industrial companies, (2) registered on the IDX and issuing annual financial reports for 2019 to 2021, (3) accounting period on an annual basis, and (4) has data on managerial ownership, institutional ownership, independent audit committee commissioners, and obtained a sample of 7 industrial companies. The sampling method is purposive sampling, which is based on annual financial reports. Good governance has been evaluated on the basis of different practices (directors, multiple directors, ownership management and audit committees) while discretionary accruals have been used as a go-between for estimating malpractice in earnings. This was achieved by using a modified Jones model (Dechow et al., 2018) to obtain results. These empirical findings are consistent with the concept of corporate governance. CEO–chair duality is significantly related to earnings management practices and thus, is noteworthy. Information obtained in this study that there is a correlation with two main areas of research, namely, corporate governance and income manipulation. Explicitly confirming that the company is on the IDX, company administration has an impact on the problem of income manipulation. The importance of this research is enhanced by the prevalence of, so-called, "wars of interest" between minority and controlling shareholders rather than between executives and owners.